The effectiveness of care bundles for reducing caesarean section safely: A systematic review and meta-analysis - Kate O’Doherty; Aileen Rothwell; Valerie Smith (PLoS ONE, 2025)
Care bundles, which consist of three or more interventions implemented together, may help address the global rise in caesarean births. The aim of this systematic review is to evaluate the effectiveness of care bundles designed to reduce caesarean section (CS). MEDLINE, CINAHL, CENTRAL and Embase were searched from January 2000 to June 2024 using terms related to CS and care bundles. Grey literature and professional body websites were also searched. Randomised or non-randomised studies reporting on pregnant or labouring women who received a care bundle designed to reduce CS safely were eligible. Data were extracted by two reviewers independently. Pre-specified outcomes included CS (overall, elective, and emergency), assisted vaginal birth, neonatal admission to intensive care, and care bundle compliance. Meta-analyses were undertaken using Review Manager 5.4 and a random effects model. Odds Ratio (OR) with 95% Confidence Interval (CI) were calculated. The certainty of the evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach. Ten non-randomised studies were included. Care bundles reduced CS overall (OR 0.83, 95% CI 0.72 to 0.97) and emergency CS (OR 0.82, 95% CI 0.68 to 0.98). No differences were observed in assisted vaginal birth (OR 1.10, 95% CI 0.91 to 1.33) or neonatal admission to intensive care (OR 1.06, 95% CI 0.56 to 2.02). Compliance to the care bundles ranged from 50% to 92%. The certainty of the evidence for all outcomes was very low. Randomised trial research is required to better assess care bundle use in reducing CS safely.